1987
DOI: 10.1136/bmj.295.6591.176
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of clinical isolates of Haemophilus influenzae in United Kingdom 1986.

Abstract: ampicillin 7-8% (6-2% P-lactamase producers and 1-6% nonproducers), tetracycline 2 , chloramphenicol 1.7%, trimethoprim 4.2%, and sulphamethoxazole 3-5%. Of the 87 capsulated strains, 15 produced P-lactamase, nine were resistantto ampicillin but did not produce P3-lactamase, and two strains, one of which produced P-lactamase, were resistant to chloramphenicol and tetracycline.Since 1977 the prevalence ofresistance to ampiciflin, chloramphenicol, and trimethoprim has increased significantly. During

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

1988
1988
1994
1994

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 13 publications
2
24
0
1
Order By: Relevance
“…influenzae type-b infections which failed to respond to ampicillin therapy prompted some of the earliest reports of resistance to antimicrobial agents in use against this species (Gunn et al, 1974). The prevalence of P-lactamase-producing H. influenzae identified from United Kingdom surveys rose from 1 -6% in 1977 (Howard et al, 1978) to 18% amongst type-b isolates and 6.2% overall in 1986 (Powell et al, 1987). In Europe, p-lactamase production is most common among type-b (64%) and non-capsulate (26%) Spanish isolates (Machka et al, 1988).…”
Section: Resistance To P-lactamsmentioning
confidence: 99%
See 4 more Smart Citations
“…influenzae type-b infections which failed to respond to ampicillin therapy prompted some of the earliest reports of resistance to antimicrobial agents in use against this species (Gunn et al, 1974). The prevalence of P-lactamase-producing H. influenzae identified from United Kingdom surveys rose from 1 -6% in 1977 (Howard et al, 1978) to 18% amongst type-b isolates and 6.2% overall in 1986 (Powell et al, 1987). In Europe, p-lactamase production is most common among type-b (64%) and non-capsulate (26%) Spanish isolates (Machka et al, 1988).…”
Section: Resistance To P-lactamsmentioning
confidence: 99%
“…The prevalence of resistance to trimethoprim in the UK reached 4.2% in 1986 (Powell et al, 1987). Few international studies have reported on resistance to trimethoprim not tested in combination with sulphamethoxazole.…”
Section: Anti-folate Agentsmentioning
confidence: 99%
See 3 more Smart Citations